The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fpls.2018.00819
|View full text |Cite
|
Sign up to set email alerts
|

Combined Drought and Heat Activates Protective Responses in Eucalyptus globulus That Are Not Activated When Subjected to Drought or Heat Stress Alone

Abstract: Aiming to mimic a more realistic field condition and to determine convergent and divergent responses of individual stresses in relation to their combination, we explored physiological, biochemical, and metabolomic alterations after drought and heat stress imposition (alone and combined) and recovery, using a drought-tolerant Eucalyptus globulus clone. When plants were exposed to drought alone, the main responses included reduced pre-dawn water potential (Ψpd) and gas exchange. This was accompanied by increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 58 publications
9
57
2
5
Order By: Relevance
“…However, the environmental factors evaluated (water stress and + 2°C in the canopy temperature) had a significant influence on the characterisation of stress. MDA is a by‐product of lipid peroxidation and is used to quantify the damage caused by ROS to cell membranes (Correia et al ). In this work, independent of treatment, the MDA content was low at 06:00 h and high at 12:00 h, as a result of the elevated level of solar radiation commonly observed at noon.…”
Section: Discussionmentioning
confidence: 99%
“…However, the environmental factors evaluated (water stress and + 2°C in the canopy temperature) had a significant influence on the characterisation of stress. MDA is a by‐product of lipid peroxidation and is used to quantify the damage caused by ROS to cell membranes (Correia et al ). In this work, independent of treatment, the MDA content was low at 06:00 h and high at 12:00 h, as a result of the elevated level of solar radiation commonly observed at noon.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct economic benefits provided by tree species, i.e., timber and non-timber products, gaming and tourism, forests have an immensurable ecological value, being the major determinants for water, oxygen, carbon, and energy balance and can be seen as a major opportunity to mitigate climate change effects [12], i.e., continued drought, increased soil and water salinization and acidification, and intensification of extreme temperatures [13]. In forest tree metabolomics research, most biological questions are indeed related to the responses towards the acclimation and adaptation to a permanently changing environment [14][15][16][17][18][19][20][21][22][23][24][25][26] as well as to the identification of potentially active components in tree species of pharmacological, agricultural, environmental, or industrial importance [27][28][29][30][31][32][33].…”
Section: Biological Question Formulationmentioning
confidence: 99%
“…In forest tree research, LC-MS instruments have also been used for untargeted secondary metabolite profiling and phytohormone quantification studies. The focus of these studies was related with abiotic stress responses [19][20][21][22][23][24]67,88,89]; and to a smaller extent to biotic stress responses [90,91] and plant growth and developmental processes [77,92,93].…”
Section: Lc-ms Metabolite Profilingmentioning
confidence: 99%
“…Among these co‐occurring stresses, the impacts of heat and drought stress combination are the most devastating (Mittler ) and have become the subject of considerable research in the recent years (Mahalingam , Lawas et al ). Research on combined heat and drought stress in model plants (Rizhsky et al , Iyer et al ) as well as in plants of agronomic importance have been reported (Simon‐Sarkadi et al , Prasad et al , Zhao et al , Templer et al , Correia et al , Sehgal et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Lawas et al 2018). Research on combined heat and drought stress in model plants (Rizhsky et al 2004, Iyer et al 2013 as well as in plants of agronomic importance have been reported (Simon-Sarkadi et al 2005, Prasad et al 2011, Zhao et al 2016, Templer et al 2017, Correia et al 2018, Sehgal et al 2018.…”
Section: Introductionmentioning
confidence: 99%